Use of innovative technologies to extend the shelf life of dairy products - V. Hruban; M. Khramov; O. Lymar; A. Pastushenko (Наукові доповіді Національного університету біоресурсів і природокористування України)
The aim of the study was to provide a comprehensive assessment of the impact of innovative technologies on the processing and treatment of dairy products in order to extend their shelf life. A comparative analysis of non-thermal methods revealed that high-pressure processing (600 MPa, 15 minutes) and pulsed electric fields (35 kV/cm, 1,000 Hz) were the most effective in inactivating microorganisms, reducing their overall count by 4.2 and 3.8 log CFU/cm³, respectively. Non-thermal techniques showed less impact on the nutritional composition of milk compared to traditional pasteurisation, preserving up to 91.8% of vitamin C and 97.2% of whey proteins. The best organoleptic properties were observed in samples treated with high-pressure processing and pulsed electric fields, scoring 4.9 out of 5 on a 5-point scale. It was also found that ultrasound treatment accelerated yoghurt fermentation by 28%-32%, high pressure shortened cheese ripening time by 30%-35%, and ultrafiltration increased the yield of acid-set cheese by 15%-18%. Among antimicrobial packaging materials, the highest activity was demonstrated by films containing silver nanoparticles (1.5%). A synergistic effect was observed when combining non-thermal processing methods with innovative packaging materials, enabling the extension of milk’s shelf life to 35 days at a temperature of 4 ± 1°C. Intelligent packaging systems with pH-sensitive indicators were developed for monitoring product freshness. To investigate the synergistic effect of combined treatments, a factorial experimental design was employed with the calculation of synergy coefficients. An analysis of nanoparticle migration from packaging materials showed that their concentration remained within permissible limits when recommended storage conditions were observed. Mathematical models were developed to predict milk shelf life based on processing and packaging parameters. An economic evaluation of the proposed technological solutions demonstrated their competitiveness in comparison with traditional methods, particularly in the production of premium-segment products